Factors Associated with Patient Safety Incident Reporting in Hospitals: A Scoping Review - Sri Rahayu; Idyatul Hasanah; Zulkahfi Zulkahfi (Lembaga Bale Literasi, 2026)
Background: Patient safety incident reporting is a key component of hospital patient safety systems because it helps identify errors, analyze root causes, and improve healthcare quality. However, incident reporting remains low in many hospitals, limiting opportunities for organizational learning and patient safety improvement. Individual, organizational, cultural, and reporting system factors may influence reporting behavior among healthcare workers. Objective: This study aimed to identify and map factors associated with patient safety incident reporting in hospitals. Methods: A scoping review was conducted following the PRISMA-ScR guideline. Literature searches were performed in PubMed, ScienceDirect, and ProQuest for articles published between 2021 and 2026. Articles were screened using Rayyan, and study quality was assessed using the Joanna Briggs Institute Critical Appraisal Tools. Results: A total of 24 studies met the inclusion criteria. Four major categories influencing patient safety incident reporting were identified: individual factors, organizational factors, patient safety culture, and reporting system factors. Patient safety culture was identified as the most influential factor, particularly teamwork, communication openness, and non-punitive responses to errors. Leadership support, staffing, workload, healthcare workers’ knowledge, and reporting systems with feedback mechanisms were also associated with reporting behavior. Conclusion: Patient safety incident reporting is influenced by multiple interrelated factors. Strengthening patient safety culture, enhancing organizational support, and improving reporting systems are essential strategies to increase incident reporting and ultimately improve the quality of patient safety in hospital settings.